Quality of life in isolated dystonia: non-motor manifestations matter. Issue 6 (9th February 2021) - Junker, Johanna; Berman, Brian D; Hall, James; Wahba, Deena W; Brandt, Valerie; Perlmutter, Joel S; Jankovic, Joseph; Malaty, Irene A; Wagle Shukla, Aparna; Reich, Stephen G; Espay, Alberto J; Duque, Kevin R; et al.
Abstract : Objective: To evaluate the relationship between health-related quality of life (HR-QoL) and both physical and psychiatric factors in a large, international, multicentre cohort of patients with isolated dystonia, the Dystonia Coalition. Methods: Natural history data from 603 patients with isolated dystonia (median age 57 years (IQR: 48 to 64 years), 67.0% women) were prospectively acquired and analysed. HR-QoL (RAND 36-Item Health Survey), severity of depressive symptoms, generalised anxiety (Hospital Anxiety and Depression Scale) and social anxiety (Liebowitz Social Anxiety Scale) were assessed. Dystonia severity (Burke-Fahn-Marsden Dystonia Rating Scale) and dystonic tremor were examined. Statistical predictors of HR-QoL were calculated using saturated path analysis. Results: Reduced HR-QoL was strongly associated with the degree of depressive symptoms and generalised and social anxiety (8/8 RAND 36 subscales, p≤0.001). Increased dystonia severity was associated with worse physical functioning, physical and emotional role functioning and social functioning (all p≤0.001). The presence of tremor correlated with worse physical functioning and pain (all p≤0.006). Younger age was associated with reduced emotional well-being and vitality (all p≤0.006). There were no HR-QoL differences between sexes. Conclusion: HR-QoL in isolated dystonia is strongly associated with psychiatric and physical features. While current standard of care focus on motor aspects of dystonia, comprehensive care should address both physical and mental aspects of health.